2013
DOI: 10.1118/1.4815478
|View full text |Cite
|
Sign up to set email alerts
|

TU‐G‐103‐09: Measurement of Planar Average Equilibrium Dose of CT

Abstract: Purpose: The planar average equilibrium dose of CT is measured using the methodology suggested by AAPM report No. 111, and compared with the traditional weighted average estimate and the new proposed equal weighted average estimate. Methods: The study used a 320 slices Toshiba Aquilion ONE scanner, three CTDI body phantoms with total length of 46.5 cm (two of them are nested 3 piece CTDI phantoms with diameters of 10, 16, and 32 cm for each piece), a Radcal Accu‐Pro electrometer, and a Radcal 0.6 cc farmer cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…CTDI protocols recommend weighting the peripheral and central doses by 2/3 and 1/3, respectively, which has been reported as a more accurate estimate than the equal weighting approach stated in TG-111. (21) This relationship is used in this work for both head and body phantoms, although the suitability of this approximation to an oval phantom is unproven. The radially-weighted DLI gives rise to the DLP CBCT (mGy.cm):…”
Section: B2 Dlp Cbct Calculationmentioning
confidence: 99%
“…CTDI protocols recommend weighting the peripheral and central doses by 2/3 and 1/3, respectively, which has been reported as a more accurate estimate than the equal weighting approach stated in TG-111. (21) This relationship is used in this work for both head and body phantoms, although the suitability of this approximation to an oval phantom is unproven. The radially-weighted DLI gives rise to the DLP CBCT (mGy.cm):…”
Section: B2 Dlp Cbct Calculationmentioning
confidence: 99%
“…For comparison consistency, the regular weighting (1/3 central, 2/3 peripheral) was utilized rather than the TG111 suggested equal weighting. 7,9,10 While using equal weighting for the central and peripheral readings would reduce the observed differences between planar average D eq and CTDI vol , measurements have shown that the regular weighting scheme is more accurate than the TG111 proposed one when it comes to predicting the planar integral dose. 10 It has been demonstrated that for a given collimation, tube potential, and filtration, the product of equilibrium dose and pitch remains constant.…”
Section: C Dose Variation With Tube Potentialmentioning
confidence: 99%
“…7,9,10 While using equal weighting for the central and peripheral readings would reduce the observed differences between planar average D eq and CTDI vol , measurements have shown that the regular weighting scheme is more accurate than the TG111 proposed one when it comes to predicting the planar integral dose. 10 It has been demonstrated that for a given collimation, tube potential, and filtration, the product of equilibrium dose and pitch remains constant. 4,7 Therefore, in order to calculate an estimate of the imaging dose during body CTp using the acquired reference data, the average planarD eq,ref measured for the reference conditions (32 × 1.2 mm collimation, standard adult filter, 0.5 pitch) needs to be scaled by the pitch ratio.…”
Section: C Dose Variation With Tube Potentialmentioning
confidence: 99%